The Prevalence of Tattoos among Students of Secondary Schools: Sociopsychological Aspects - Sobkin V.S; Lykova T.A (Moscow State University of Psychology and Education, 2021)
The article focuses on the following issues: the prevalence of tattoos among adolescents; gender and age characteristics of their motivation for tattooing; the specifics of social behavior of adolescents with tattoos; and the occurrence of tattoos among adolescents with deviant behavior. The sample consisted of 32714 students of grades 7-11, of which 1517 people confirmed having images on the body. The data was collected using an anonymous questionnaire survey. It is shown that with the transition from elementary school to high school the proportion of students with tattoos increases. At the same time, the intensity of familiarization with the tattoo culture in high school age among girls is higher than among boys. The article describes the value and motivational attitudes that determine the role of tattoos as a symbolic means of manifestation of a teenager's attitude to sexual challenges. As it is revealed, in early adolescence the desire to get a tattoo is determined mainly by self-assertion and the search for group identity. By 9th grade, a tattoo is more often used to express individuality. In general, teenagers with tattoos have lower academic performance and are less likely to comply with school rules. Such abnormal behavior of teenagers with tattoos and their aspirations for social leadership cause bullying from classmates. It was found that deviant forms of behavior, such as profanity, alcohol and drug use, fighting, are much more common among students with tattoos. Tattoos are analyzed as a means of symbolic expression of belonging to a certain type of teenage subculture. adolescence, adolescent subculture, tattoo, motivation, sign mediation of mental processes, behavioral styles, deviations